2018
DOI: 10.1002/app.46732
|View full text |Cite
|
Sign up to set email alerts
|

Release behavior of a polyanion‐crosslinked chitosan‐poly(N‐isopropylacrylamide) gel thermoresponsive material

Abstract: A novel type of temperature‐responsive hydrogel with sensitive release performance of an encapsulated compound was obtained. The temperature‐responsive hydrogel with a sensitive state change between 32 °C and 29 °C was prepared by physically crosslinking chitosan with a polyanion of tripolyphosphate and linear poly(N‐isopropylacrylamide) (PNIPAAm). Cyanocobalamin was used as a model drug and was encapsulated in the prepared hydrogel. The swelling ratio and release behavior of cyanocobalamin were evaluated. Hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The transmittance results showed that the LCST of pure PNIPAAm was around 29.5 • C, and the difference between different formulations was not obvious. From this, it can be determined that the LCST of the semi-IPN hydrogel samples ranged from 29 to 30 • C, which is similar to the range already reported for the LCST of PNIPAAm [37,42] and consistent with the DSC data. where 0 t M M is the fraction release of spores in time t, k is the release rate constant, and n is the diffusion exponent of the release system.…”
Section: Thermosensitive Behavior Of Semi-ipn Hydrogelssupporting
confidence: 88%
“…The transmittance results showed that the LCST of pure PNIPAAm was around 29.5 • C, and the difference between different formulations was not obvious. From this, it can be determined that the LCST of the semi-IPN hydrogel samples ranged from 29 to 30 • C, which is similar to the range already reported for the LCST of PNIPAAm [37,42] and consistent with the DSC data. where 0 t M M is the fraction release of spores in time t, k is the release rate constant, and n is the diffusion exponent of the release system.…”
Section: Thermosensitive Behavior Of Semi-ipn Hydrogelssupporting
confidence: 88%
“…The microcapsule structure effectively prolongs the release and diffusion of CA, and with the accumulation of CA release, the release rate gradually slows down. Ueoka and Mohammadi et al [32,43] have also noticed the effect of temperature and stated that high temperature can control the release of antibacterial agents and low temperature can delay its effect. Figure 6B shows the sustained release profile of SiO2-CA microcapsules at different humidity levels (90%, 70%, and 50% RH).…”
Section: Sustained-release Performance Analysismentioning
confidence: 99%
“…57 Another study reported a similar crosslinking of chitosan with a polyanion of tripolyphosphate and poly(N-isopropylacrylamide) (PNIPAAm) possessing thermoresponsive behavior. 58 It is possible to tailor such crosslinking as per the application since it is triggered by a pH change that causes protonation and deprotonation of the ionic functional groups. In a few cases, it may also form in situ hydrogels due to physiological pH, for example, chitosan undergoes ionic interaction with negatively charged βglycerophosphate to form thermosensitive in situ hydrogels for the delivery of 188 Re-Tin colloid, 59 doxorubicin, 59 and ibuprofen.…”
Section: Hydrogel Cross-linking Methodsmentioning
confidence: 99%
“…Thermoresponsive xyloglucan/cellulose nanocrystal hydrogels present an LCST close to the body temperature since they progressively convert from sol to gel state at 35 °C . There are numerous reports on the thermoresponsive behavior of chitosan-based hydrogels showing sharp phase transition above the LCST or around body temperature that depict several applications. ,,,,, Moreover, rheological measurements such as the temperature sweep test also determine the thermos-reversible nature of the hydrogels utilized to determine the thermoresponsive behavior of gelatin/gellan and chitosan/β-glycerophosphate hydrogel. Here, G ′ is always greater than G ′′, which increases gradually and becomes resistant to temperature change.…”
Section: Stimuli-responsivenessmentioning
confidence: 99%
See 1 more Smart Citation